2014
DOI: 10.5334/tohm.207
|View full text |Cite
|
Sign up to set email alerts
|

The Progression of Posterior Cortical Atrophy to Corticobasal Syndrome: Lumping or Splitting Neurodegenerative Diseases?

Abstract: Background: Posterior cortical atrophy is a clinical syndrome that is characterized by the progressive loss of visuospatial integration and is associated with neurodegenerative conditions.Case Report: We describe a 60-year-old female with simultanagnosia, oculomotor apraxia, and optic ataxia for which she received an initial clinical diagnosis of posterior cortical atrophy. Three years later, she developed Balint's syndrome, Gerstmann's syndrome, left alien hand syndrome, smooth asymmetric (left) rigidity, cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Besides corticobasal degeneration, CBS can also be caused by such as progressive supranuclear palsy, AD, Pick’s disease, FTLD with TDP-43 inclusions, mutations in GRN or MAPT , DLB, and CJD [ 10 ]. Considering current clinical criteria and various pathological etiologies for PCA and CBS, there is considerable overlap, meaning that some patients may fulfill criteria for both syndromes, or develop from one syndrome to the other [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides corticobasal degeneration, CBS can also be caused by such as progressive supranuclear palsy, AD, Pick’s disease, FTLD with TDP-43 inclusions, mutations in GRN or MAPT , DLB, and CJD [ 10 ]. Considering current clinical criteria and various pathological etiologies for PCA and CBS, there is considerable overlap, meaning that some patients may fulfill criteria for both syndromes, or develop from one syndrome to the other [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least three pathologically diagnosed CBD patients and one patient without pathologic diagnosis have been reported with a PCA syndrome as a presenting symptom followed by signs of CBS (i.e. asymmetric apraxia and parkinsonism) later in the course of the illness (two patients studied by Tang-Wai et al, 2003; one patient by Lee et al, 2011; one patient by Giorelli, Losignore, Bagnoli, Difazio, & Zimatore, 2014). Finally, a subgroup of PCA patients has been found to show motor features commonly associated with CBS (i.e.…”
Section: Cbs and Pcamentioning
confidence: 99%
“…Pathologic studies have revealed that PCA is most often the clinical expression of an atypical form of Alzheimer pathology [2], named the visual variant. More rarely, PCA may be associated to other neurodegenerative etiologies, such as corticobasal degeneration, dementia with Lewy bodies, prion disease (Creutzfeldt-Jakob disease), and subcortical gliosis [1,[3][4][5]. The clinical phenotype may vary according to the etiology, and may include elements of the Balint's syndrome (optic ataxia, oculomotor apraxia, simultagnosia).…”
Section: Introductionmentioning
confidence: 99%